Studi Tentang Kinerja Guru Penjasorkes Sekolah Dasar Negeri Se-Kecamatan Nguter Kabupaten Sukoharjo Tahun 2021 - Adhinata, Faisal Nur; Qoriah, Anirotul (Universitas Negeri Semarang, 2023)
The purpose of this study was to determine the purpose of this study to determine the performance of Physical Education teachers in Public Elementary Schools in Nguter District, Sukoharjo Regency in 2021 seen from lesson planning, implementation of learning and implementation of learning evaluation. The research method uses a quantitative descriptive approach. Retrieval of research data using a questionnaire. This research data processing technique uses a rating scale to make it easier to process data from the results of respondents' answers. This study obtained results from the low average performance of Public Elementary School Penjasorkes teachers in Nguter District, Sukoharjo Regency in 2021. This can be seen from the results of respondents' answers, namely: indicator answers are always or a value of 4 on aspects of learning planning (43.14%), implementation of learning (59.47%) and implementation of learning evaluation (62.93%). The conclusion from the results of the research is that the performance of Primary School Physical Education teachers in Nguter Sub-district, Sukoharjo Regency in 2021 in terms of the implementation of learning is low, in terms of the aspect of learning planning it is low, and in terms of the implementation of the evaluation of learning it is moderate.